An Aquatic Pseudo-Four-Component Reaction for the Synthesis of Highly Substituted Thiophenes - Zali-Boeini, Hassan; Ghani, Maryam (Synthesis, 2013)
A novel and simple procedure was developed for the construction of fully substituted thiophenes. A series of α-haloacetophenone derivatives were converted into fully substituted thiophenes by treatment with sodium sulfide in the presence of 1,8-diazabicyclo[5.4.0]undec-7-ene and sodium iodide in aqueous ethanol under aerobic conditions. A mechanism for the reaction is proposed.
Keywords: sulfur; heterocycles; alkyl halides; coupling; dehydrogenation; multicomponent reactions